2021
DOI: 10.3389/fpls.2021.687652
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Challenges to Enhancing Experimental Plant Biology With Computational Modeling

Abstract: The study of complex biological systems necessitates computational modeling approaches that are currently underutilized in plant biology. Many plant biologists have trouble identifying or adopting modeling methods to their research, particularly mechanistic mathematical modeling. Here we address challenges that limit the use of computational modeling methods, particularly mechanistic mathematical modeling. We divide computational modeling techniques into either pattern models (e.g., bioinformatics, machine lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…As highlighted by Roose et al. (2016), the combination of imaging and modeling allows model generation based on real data, with the caveat that such models might always be specifically adapted to a certain experimental system (Dale et al., 2021). For this work specifically, we found that inclusion of bulk soil heterogeneity was necessary to characterize the experimental system using an RT model, and that doing so increased our understanding of the dynamics of water redistribution and O 2 transport as a function of root uptake.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted by Roose et al. (2016), the combination of imaging and modeling allows model generation based on real data, with the caveat that such models might always be specifically adapted to a certain experimental system (Dale et al., 2021). For this work specifically, we found that inclusion of bulk soil heterogeneity was necessary to characterize the experimental system using an RT model, and that doing so increased our understanding of the dynamics of water redistribution and O 2 transport as a function of root uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical modeling has proven very powerful in providing unprecedented insights into physiological mechanisms ( Dale et al., 2021 ). Here, we continued our analyses of the properties of transport networks.…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental basis for the correct description of complex biological systems, such as we find in plants, is the mathematical representation of the individual entities. Only in this way is it possible to use computers to simulate the dynamics of the systems in mechanistic mathematical models (Dale et al, 2021). Such models are often designed to mimic the physiological reality in order to support experimental data (see for instance, Chen et al, 2012;Hills et al, 2012;Blatt et al, 2014;Morris, 2018;Holzheu and Kummer, 2019;Iosip et al, 2020;Huang et al, 2021;Jezek et al, 2021).…”
Section: Mechanistic Mathematical Modelingmentioning
confidence: 99%
“…They therefore contribute to the efficient use of available resources for research. Nevertheless, despite the huge potential of mechanistic mathematical models and computational cell biology simulations, there are significant obstacles to implementing these approaches (Dale et al, 2021). Some of the biggest challenges are outlined in the following.…”
Section: Mechanistic Mathematical Modelingmentioning
confidence: 99%